F61. TRIVIAL TRANSITIONS? SIPS-DEFINED CONVERSIONS TO PSYCHOSIS: ONE YEAR OUTCOME. (9th April 2019) - Sykes, Laura Yoviene; Ferrara, Maria; Cahill, John; Addington, Jean; Bearden, Carrie; Cadenhead, Kristen; Cannon, Tyrone; Cornblatt, Barbara; Perkins, Diana; Mathalon, Daniel; Seidman, Larry; Tsuang, Ming; et al.
Abstract: Background: Although the clinical high risk (CHR) for psychosis paradigm has become well-established over the past two decades, one key component has received surprisingly little direct investigative attention: the validity of the conversion to psychosis or transition criteria. This lack of evidence is surprising because many CHR treatment and prediction studies rely on the conversion measure as an outcome. In the absence of such evidence, some observers have raised the possibility that conversions from CHR may be trivial. The aim of this study is to evaluate the predictive validity of the transition to psychosis as measured by the Structured Interview for Psychosis-Risk Syndromes (SIPS) in CHR individuals. To our knowledge, this is the first study to examine the CHR conversion to psychosis at one-year follow-up. It is hypothesized that CHR participants whose conversion to frank psychosis was ascertained by SIPS (SIPS CV) will show similar diagnostic stability and severity of illness compared to the FEP sample and will differ significantly from SIPS Non-Converters (NCV) on clinical severity. Methods: Participants included 33 SIPS Converters (CV) (met criteria for conversion to frank psychosis (COPS) on SIPS) and 399 CHR NCV both from the North American Prodromal Longitudinal Study (NAPLS 2), as well as a sample of 67 separately-ascertained first-episode psychosis (FEP) patients from the STEP Coordinated Specialty Care (CSC) program in New Haven, CT. Comparisons using Chi-square and ANOVA were made at baseline and one-year follow-up on variables from demographic, diagnostic stability (SCID) and available measurement domains relating to severity of illness (psychotropic medication and resource utilization). Results: The principal findings of the present study are: 1) large majority of cases in both SIPS CV (n=27/33, 81.8%) and FEP (n=57/67, 85.1%) samples continued to have current psychosis diagnoses at one year follow up, 2) exposure to antipsychotic medication was higher in SIPS CVs (n=17/32, 53.1%) compared to SIPS NCVs (n=81/397, 20.4%), and similar as compared to FEP cases (n=39/65, 60%), 3) at follow up, SIPS CV had higher rates of resource utilization (any psychiatric hospitalizations, day hospital admissions, and ER visits) than SIPS-NCV and were similar to FEP in most categories. Discussion: The results suggest that the SIPS definition of psychosis onset carries substantial validity in that those with SIPS-defined psychosis demonstrate similar diagnostic stability and severity of illness at one-year follow as a first episode sample and greater severity of illness as compared to a SIPS-defined CHR con-converting sample. Limitations include the lack of functional assessments at follow-up in the SIPS-CV. Additional studies are needed to further validate the CHR vs transition to psychosis distinction. Since many patients who come to baseline evaluation for CHR are discovered to have previously unrecognized frank psychosis, future studies should aim to obtain additional evidence by following this important group.